2021
DOI: 10.3390/diagnostics11040591
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Detection of Cranio-Spinal Differences between Skeletal Classification Using Cephalometric Radiography

Abstract: The aim of this study was to reveal cranio-spinal differences between skeletal classification using convolutional neural networks (CNNs). Transverse and longitudinal cephalometric images of 832 patients were used for training and testing of CNNs (365 males and 467 females). Labeling was performed such that the jawbone was sufficiently masked, while the parts other than the jawbone were minimally masked. DenseNet was used as the feature extractor. Five random sampling crossvalidations were performed for two dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…In this study, four different classifiers are used to evaluate the above feature sets: k-NN [ 5 ], extreme learning machine (ELM) [ 6 ], support vector machine (SVM) [ 7 ], and random forest algorithm (RF) [ 8 ].…”
Section: Model Experiments and Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, four different classifiers are used to evaluate the above feature sets: k-NN [ 5 ], extreme learning machine (ELM) [ 6 ], support vector machine (SVM) [ 7 ], and random forest algorithm (RF) [ 8 ].…”
Section: Model Experiments and Results Analysismentioning
confidence: 99%
“…Therefore, how to effectively relieve the pain response after spinal fusion has become the focus and difficulty of clinical nursing. Multimodal analgesia is a new analgesic model, which mainly gives play to the superposition or synergy of analgesia through the combined use of a variety of drugs or technologies with different analgesic mechanisms, so as to reduce the dosage of a single analgesic drug and reduce the adverse analgesic reactions [ 5 ]. Studies have shown that [ 2 ] when patients undergoing spinal fusion were given multimodal analgesia during the perioperative period, the VAS at different time points after operation was significantly lower than that of the previous use of patient-controlled intravenous analgesia pump alone ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Análisis fotográfico y radiográfico para predicciones de piezas a extraer con machine learning models 40 . Evaluación de las diferencias cráneo espinales entre las clases esqueléticas con CNN (DenseNet121) 41 . Mejoras en el diagnóstico esquelético para ortodóncia a través del CNN with a modified Desenet 42 ; en el análisis cefalométrico automatizado 43 , identificación y análisis de puntos de referencia faciales y cefalométricos con utilización de algoritmos como YOLO 44 y Bayesian Convolutional Neural Networks (BCNN) 45 y últimamente en la monitorización del tratamiento ortodóncico 46 .…”
Section: Revisión Y Discusiónunclassified
“…In the field of dentistry, research has been conducted about the detection and classification of anatomical variables [ 9 , 10 ], periapical lesions [ 11 , 12 ], dental caries [ 13 , 14 , 15 ], periodontitis [ 16 ], and benign tumors and cysts [ 17 ]. Deep learning analysis has also been applied to cephalometric images, such as detection of landmarks [ 18 ], prediction of the necessity for orthognathic surgery [ 19 ], and detection of cranio-spinal differences [ 20 ]. In relation to extraction of the mandibular third molar, attempts have been made to segment the teeth and the inferior alveolar nerve (IAN) [ 21 , 22 ], and, recently, a study to determine the difficulty of extraction was also conducted [ 23 ].…”
Section: Introductionmentioning
confidence: 99%